Strategi Komunikasi Bank BNI Cabang Parepare Membangun Budaya Organisasi di Masa Pandemi Covid-19 - Ahmad Sultra Rustan; Mifdah Hilmiyah; Awalia, Nur Awalia (Communication and Islamic Broadcasting Studies IAIN Parepare, 2023)
The organization is a system that coordinates various forms of activity and common goals to achieve the expected goals. Running an organization is largely determined by the organizational culture that is formed and changes for adaptation. This study aims to find out how the organizational culture of Bank BNI Parepare Branch was before the Covid-19 pandemic, and what was the communication strategy for transforming the organizational culture of Bank BNI Parepare Branch during the Covid-19 pandemic. The results of this study indicate that: (1) The organizational culture of Bank BNI Parepare Branch before the Covid-19 pandemic included several activities at Bank BNI to shape the reality of organizational culture before the pandemic, with the aim of creating good interaction and communication, including: Morning Breafing, and Family gathering. There is also organizational performance, namely in terms of appearance, spatial planning, this performance is a routine that is chosen as a culture attached to the organization. Changes during a pandemic are due to the obligation to implement established health protocols; (2) According to informants, the communication strategy for organizational cultural transformation of Bank BNI Parepare Branch during the Covid-19 pandemic was by determining the right communicators, namely the HR and general units, delivering policies or messages through written communication by adding symbols or signs as the chosen communication technique, as well as delivery media by utilizing various social media platforms and bulletin boards.